Sleep quality in nursing students - Ribeiro, Maria Isabel (2015)
Introduction: The quality of sleep is imperative to maintain the physical and psychological well-being of human beings. University life is an inevitable change factor of habits and lifestyles with particular influence on students’ sleep quality (Kloss, Nash, Horsey & Taylor, 2011). Objectives: To evaluate sleep quality in nursing students from Bragança School of Health. To find out the time each student takes to fall asleep. To calculate students’ hours of sleep. Materials and Methods: A sample of 138 students was collected from a total of 361 students enrolled in the nursing degree in 2014/2015. The Quality Index Pittsburgh Sleep survey was used to collect the data during October 2014 to January 2015. This instrument has a maximum score of 21 points. For a score greater than five points, the quality of sleep was considered bad. Most students were female (82.6%) with ages between 18 and 20 years (62.3%) and didn’t live with their parents (66.0%). Results and Discussion: Most respondents classify his/her sleep quality as "good". On average, students sleep 6.7 hours per night. According to referenced literature, healthy adults should sleep between 7 to 9 hours per night. On average, students take about 20 minutes to fall asleep. According PaConclusion: Sleep problems are common among university students, since they are exposed to changes in their lifestyle, adopting behaviors that affect sleep quality. However, according to the results, most students consider their sleep quality as good. References: Kloss, J.; Nash, C.; Horsey, S. & Taylor, D. (2011). The delivery of behavioral sleep medicine to college students. J Adolesc Health, 48(6):553-61. Pascotto, A. & Santos, B. (2013). Avaliação da qualidade do sono em estudantes de ciências da saúde. J. Health Sci Inst, 31(3):306-10. scotto e Santos (2013) the majority college students take about 15 minutes to fall asleep